1993
DOI: 10.1002/mrd.1080350114
|View full text |Cite
|
Sign up to set email alerts
|

Purine control of mouse oocyte maturation: Evidence that nonmetabolized hypoxanthine maintains meiotic arrest

Abstract: Hypoxanthine is present in preparations of follicular fluid and has been shown to suppress the spontaneous meiotic maturation of mammalian oocytes in vitro. The present experiments examined the possible role of hypoxanthine metabolism in mediating this meiotic arrest. Four putative inhibitors of the enzyme, hypoxanthine phosphoribosyltransferase (HPRT), which metabolizes hypoxanthine to inosine monophosphate, were tested on lysates of oocyte-cumulus cell complexes. At a concentration of 1 mM, 6-mercapto-9-(tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 36 publications
0
41
0
4
Order By: Relevance
“…Considering the fact that CM maintained oocyte meiotic arrest more efficiently (P!0.001) than FM suggests the possibility that meiotic arrest could be sustained by a secreted inhibitory factor of follicular origin , Downs 1993) causing resistance to EREG or EGF stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the fact that CM maintained oocyte meiotic arrest more efficiently (P!0.001) than FM suggests the possibility that meiotic arrest could be sustained by a secreted inhibitory factor of follicular origin , Downs 1993) causing resistance to EREG or EGF stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Of the blastocysts analyzed, only 6% demonstrated targeting of both IMPDH II alleles, strongly suggesting that loss of the IMPDH type II enzyme does not permit the further development of fertilized ova. Previous studies have suggested a critical role for purines, especially for guanosine and hypoxanthine, in the maintenance of oocytes in meiotic arrest (29). Inhibitors of IMPDH such as MPA induced premature meiotic maturation and resulted in a significant loss of implantation capacity and viability after implantation (30).…”
Section: Discussionmentioning
confidence: 99%
“…Transcription in oocytes depends on the presence of attached CCs (De La Fuente & Eppig 2001). In addition, the maintenance of oocyte arrest before recruitment also relies on the contribution of autocrine and paracrine factors synthesized in GCs, including cAMP/cGMP (Webb et al 2002, Wigglesworth et al 2013, Shuhaibar et al 2015, purine (Downs 1993), kit ligand (Ye et al 2009), and NPR2 , Tsuji et al 2012, Wigglesworth et al 2013. Oocytes from antral follicles resume and complete meiosis spontaneously after removal of surrounding CCs (Buccione et al 1990, Mehlmann 2005, suggesting that CCs control oocyte nuclear maturation.…”
Section: Introductionmentioning
confidence: 99%